2022
DOI: 10.1155/2022/7122643
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Sciatica Pain and Treatment Methods among Adults in Saudi Arabia

Abstract: Background. Sciatica is a relatively common condition, with a lifetime incidence varying from 13% to 40%. The corresponding annual incidence of an episode of sciatica ranges from 1% to 5%. The exact cause of sciatica is unknown to this day; treatment methods and practices differ between individuals based on their cultural background, socioeconomic status, and religious beliefs. This study aimed to assess the knowledge and attitude toward sciatica pain among adults in Saudi Arabia. Methods. A cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The study indicated that while the adult population's attitude about sciatica was sufficient, the information was lacking. It has been demonstrated that adults with pre-existing diseases who reside in cities have better attitudes and knowledge (Hashem et al, 2022). Another Saudi Arabian study that was conducted in 2016 looked into Saudi patients' understanding of back pain and spinal problems.…”
Section: Resultsmentioning
confidence: 99%
“…The study indicated that while the adult population's attitude about sciatica was sufficient, the information was lacking. It has been demonstrated that adults with pre-existing diseases who reside in cities have better attitudes and knowledge (Hashem et al, 2022). Another Saudi Arabian study that was conducted in 2016 looked into Saudi patients' understanding of back pain and spinal problems.…”
Section: Resultsmentioning
confidence: 99%
“…There is a scarcity of data on sciatica in Saudi Arabia, highlighting the need for more studies exploring sciatica among the Saudi population since the prevalence of low back pain is high (63.8- 89%) [ 10 , 11 ]. One study evaluating sciatica prevalence in Saudi Arabia found it to be 13.5%; the factors connected with high prevalence were found to be the 35-49 years age group, Saudi nationality, having a bachelor's degree, and being a nonhealthcare worker [ 11 , 12 ]. Moreover, the knowledge about sciatica was reported inadequate in Saudi Arabia despite good attitude [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study evaluating sciatica prevalence in Saudi Arabia found it to be 13.5%; the factors connected with high prevalence were found to be the 35-49 years age group, Saudi nationality, having a bachelor's degree, and being a nonhealthcare worker [ 11 , 12 ]. Moreover, the knowledge about sciatica was reported inadequate in Saudi Arabia despite good attitude [ 12 ]. This review presents available knowledge about sciatica, including clinical manifestations, diagnosis and treatment modalities, prognosis, and complications.…”
Section: Introductionmentioning
confidence: 99%